Rapid Molecular Karyotyping for Products of Conception by BACs-on-beads Technology - Preyaporn Onsod (2022)
Aim: Bacterial artificial chromosomes (BACs)-on-beads (BoBs) technology detects aneuploidy, chromosome gains, and losses. The Prenatal™ BoBs detect common aneuploidies and nine microdeletion syndromes. The KaryoLite™ BoBs additionally detect alterations in the p and q arm of all chromosomes. We evaluated BoBs technology for the product of conception (POC) screening. Materials and methods: A total of 265 fresh POC were evaluated by the different BoBs (233 KaryoLite™ BoBs, nine Prenatal™ BoBs, and 23 of both). Results: BoBs detected chromosomal abnormalities in 142 samples (53.58%). The most frequent chromosome abnormality was trisomy 21 (17.61%), followed by monosomy X, trisomy 16, and trisomy 22 (14.08%). Twenty-three samples (13 normal and 10 abnormal), which used both KaryoLite™ and Prenatal™ BoBs kits, were concordant. Moreover, BoBs techniques had no failure rate. Conclusion: BoBs technology is a potentially useful method for diagnosing common aneuploidies and microdeletion syndromes in conception products. This method’s advantage over cell culture includes quicker results and a lower failure rate.